2018
DOI: 10.1016/j.jclepro.2018.06.173
|View full text |Cite
|
Sign up to set email alerts
|

Life cycle assessment to compare the environmental impacts of different wheat production systems

Abstract: The share of fossil-based resources in the implementation of agricultural activities in Iran is very high. In this context, it is important to determine the environmental impacts of energy use in agricultural activities. The purpose of this study was to evaluate and compare the energy consumption and total environmental impacts of irrigated and rainfed wheat production in central Iran, Mahyar plain. For this purpose, data were collected from 120 irrigated and 90 rainfed wheat farms in three different farm size… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
16
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 79 publications
(29 citation statements)
references
References 48 publications
1
16
0
Order By: Relevance
“…Furthermore, nitrogen fertilizers have also the highest negative effect on the resource depletion damage category followed by diesel fuel consumption. Our results are in line with the studies of Payandeh et al [45] and Taki et al [46]. Furthermore, the description of corn production indices through different impact assessment methodologies is presented in Table 4.…”
Section: Step Four-interpretation Of Lca Resultssupporting
confidence: 92%
“…Furthermore, nitrogen fertilizers have also the highest negative effect on the resource depletion damage category followed by diesel fuel consumption. Our results are in line with the studies of Payandeh et al [45] and Taki et al [46]. Furthermore, the description of corn production indices through different impact assessment methodologies is presented in Table 4.…”
Section: Step Four-interpretation Of Lca Resultssupporting
confidence: 92%
“…The north region yielded higher environmental indexes that might attribute to N application rate, irrigation times, and seasonal precipitation ( Qiu et al, 2008 ; Liu et al, 2020 ). Our LCA results also indicated that irrigation and fertilization have a significant impact on environmental damages, such as GWP, emphasizing the need to decrease the intensity of input energy for sustainable wheat production ( Taki et al, 2018 ).…”
Section: Discussionmentioning
confidence: 66%
“…Comparable with other C 3 cereal crops, the productivity and agronomic input use efficiency of wheat is largely affected by many environmental and managerial factors, such as growing season temperature, irrigation methods, and N fertilization rate ( Fan et al, 2018 ). In addition, a lot of fossil fuel energy is used for producing agronomic inputs, such as chemical fertilizers, leading to severe environmental pollution, particularly, in those developing countries ( Taki et al, 2018 ). Information abounds with individual field studies investigating the impacts of one or two factors on wheat productivity and physiology at a single site ( Zwart and Bastiaanssen, 2004 ; Qin et al, 2015 ).…”
Section: Introductionmentioning
confidence: 99%
“…For emerging technologies and products, identifying environmental hotspots and providing information for decision-makers are seen as crucial starting points for sustainable product and process development [29,33]. Studies applying environmental hotspot analysis of various production systems of established technologies or process pathways can be found in the literature (e.g., in agricultural systems [39][40][41], food systems [38,[42][43][44], wastewater treatment [45,46], etc.). Besides investigating environmental aspects, approaches considering social aspects, such as sustainability hot spot analysis (SHSA), are also available in the literature [43].…”
Section: Hotspot Analysismentioning
confidence: 99%